Service responses for older high-risk drug users: a literature review - Atkinson, Colin (Report, 2016)
This report identifies and reviews the academic literature on service responses for older high-risk drug users. It aims to identify the key literature on the older high-risk drug user, distil from this literature the main characteristics of older drug users and their needs, and provide an account of the service responses to older drug users to inform planning and policy for Scotland’s older drug using population.